Complete Heart Block In Pregnancy: A Case Report - Yafi, Dhanang Ali; Noviani, Cloudia; Saputri, Rahmi Eka; Purnawarman, Adi; Andalas, Mohammad; Yusmalinda, Yusmalinda (The Indonesian Heart Association, 2021)
Background: Complete heart block occurs due to various pathological conditions that cause an infiltration, fibrosis, or lose the connection from a part of the cardiac conduction system. Complete heart block in pregnancy is often caused by congenital anomalies. Around 30% cases, complete heart block remain asymptomatic and not detected until adulthood and may present in pregnancy state and puerperium. When the reversible cause of the AV Block cannot be found, the permanent pacemaker or temporary pacemaker may be indicated when the patients show the symptoms. Case Illusration: A-21 year old female, G2P0A1 preterm pregnancy (27-28 weeks) with bradycardia. From electrocardiograph examination revealed Total AV Block with junctional escape rhytym. Transthoracic echocardiogram shows massive tricuspid regurgitation, early phase of peripartum cardiomyopathy and ejection fraction 36-40%. Caesarean section was peformed due to PPROM. A male baby was born with birth weight of 1100 grams, 32 centimeters of body length and APGAR score of 7/9. The baby was died in NICU on day care 4th, with suspected respiratory problem. Conclusion: Complete heart block in pregnancy is a rare condition. This condition could remain asymptomatic and not detected until pregnancy. Multidisciplinary approach, close monitoring of the symptoms and cardiac functions are needed for patients with CHB.